Ultrasonography of the prenatal and neonatal brain - Timor-Tritsch, Ilan E. (McGraw-Hill, 2001)
This book combines a comprehensive ultrasound imaging of fetal and neonatal brains. Key Topics: It covers the embryology and development of the fetal brain as well as normal and abnormal pathology in fetal and neonatal heads. Nearly 250 line drawings are included. Market: Physicians, residents, medical students.